Fetal Kidney Length: Can be a New Parameter for Determination of Gestational Age in 3rd Trimester (TAJ: Journal of Teachers Association, 2009)
Ultrasound provides an accurate & objective method of determining fetal age in utero. A prospective study was done in 102 pregnant women after 30 weeks of pregnancy whose gestational ages were confirmed by early USG. (